Pengaruh Komunikasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Mitra Butterindojaya - Nathania Mulkan -; Yeni Ariesa - (Jurnal Ekonomi Bisnis Manajemen Prima, 2020)
The research was conducted at PT Mitra Butterindo Jaya as the object of the research. PT. Mitra Butterindo Jaya is a company engaged in the distribution of cake ingredients. For this study, researchers only took special research employees at the Medan head office in charge of the sales of PT. Mitra Butterindo Jaya. In interviews and preliminary research observations, there were problems with poor employee performance, such as the number of employees who did not complete their tasks on time, decreased employee accuracy in carrying out their duties and responsibilities within the company and difficulties in cooperation between employees. This also resulted in a decrease in sales experienced by the company. The problem with communication problems is the clarity of communication between employees that has not been going well, the communication that is carried out is often not correct in conveying language and the flow of communication that is carried out is still often an error. This results in frequent errors in carrying out work. The total population of 80 people and 30 people were taken from other companies for validity and reliability testing. Theories used to support research are human resource management theories related to discipline, work stress and compensation for performance. The research method used is a quantitative approach with quantitative descriptive research type. Methods of data collection by interview, distribution of questionnaires and documentation study. The analytical method used is multiple linear regression, coefficient of determination and simultaneous testing (F-test) (72,231> 3,12) with value and partially (t-test) (6,730> 1,991) and (2,163> 1,991). The results showed that communication and work discipline simultaneously and partially had a significant positive effect on employee performance with a determination coefficient of 64.3% which affected employee performance variables.